The Arendelle Cup - David, Erica (David, Erica. Anna & Elsa, 2015)
"People come from far and wide to compete in the Arendelle Cup, an annual sleigh race that runs through the mountains and forests around the snowy kingdom. This year, Anna and Elsa are going to race for the first time! But when another team takes a shortcut on an unsafe path, Anna, Elsa, and Sven join up with the defending champs to rescue the cheaters!"--Back cover.